2018
DOI: 10.1152/ajprenal.00050.2018
|View full text |Cite
|
Sign up to set email alerts
|

Role of WNK4 and kidney-specific WNK1 in mediating the effect of high dietary K+ intake on ROMK channel in the distal convoluted tubule

Abstract: With-no-lysine kinase 4 (WNK4) and kidney-specific (KS)-WNK1 regulate ROMK (Kir1.1) channels in a variety of cell models. We now explore the role of WNK4 and KS-WNK1 in regulating ROMK in the native distal convoluted tubule (DCT)/connecting tubule (CNT) by measuring tertiapin-Q (TPNQ; ROMK inhibitor)-sensitive K currents with whole cell recording. TPNQ-sensitive K currents in DCT2/CNT of KS- WNK1 and WNK4 mice were significantly smaller than that of WT mice. In contrast, the basolateral K channels (a Kir4.1/5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…The findings were confirmed by Wu et al (2020) , who reported that DCT/CNT cells were more sensitive than those of the CCD to changes in angiotensin II signaling. ROMK currents have also been observed in this segment, and their activity is increased in animals fed a K-rich diet ( Zhang et al, 2017 ; Wu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The findings were confirmed by Wu et al (2020) , who reported that DCT/CNT cells were more sensitive than those of the CCD to changes in angiotensin II signaling. ROMK currents have also been observed in this segment, and their activity is increased in animals fed a K-rich diet ( Zhang et al, 2017 ; Wu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 93%
“…The DCT is recognized by the convolutions and, in favorable cases, by an attached thick ascending limb and/or glomerulus. The tubule eventually straightens and narrows abruptly at a point considered to represent the junction between the DCT2 and the CNT ( Nesterov et al, 2012 ; Wu et al, 2018 ). We opened the tubule at various points along its length, both proximal and distal to this narrowing, and made whole-cell recordings under conditions favorable to the detection of ENaC currents.…”
Section: Resultsmentioning
confidence: 99%
“…WNK bodies become prominent when NCCs are activated by dietary K ϩ restriction ( 29), yet genetically engineered models have shown that NCC activity and WNK body formation can be dissociated. For example, NCC activity is high when WNK bodies are absent in mice lacking KS-WNK1 or in models of PHAII due to wnk1 or wnk4 mutations (11,33,36). To date, the relevance of WNK bodies to WNK-SPAK/OSR1 signaling has remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the relevance of WNK bodies to WNK-SPAK/OSR1 signaling has remained elusive. Wu et al (36) provided functional data showing that the inhibition of NCC upon dietary K ϩ loading is blunted in mice lacking KS-WNK1. This observation is consistent with preliminary data provided by Boyd-Shiwarski et al (5), who found that the ability of KS-WNK1deficient mice to reduce NCC phosphorylation in hyperkalemia and to increase NCC phosphorylation in hypokalemia are both compromised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation